Pembentukan Sekolah Tangguh Bencana di SD Muhammadiyah Sokonandi: Disaster-Resilient School Initiative at SD Muhammadiyah Sokonandi - Puspito, Heri; Listyaningrum, Tri Hapsari (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2025)
Yogyakarta experiences high seismic activity due to its proximity to the tectonic plate convergence zone in the Indian Ocean. SD Muhammadiyah Sokonandi, a private school in Yogyakarta, requires support to become a Disaster-Safe Educational Institution (Satuan Pendidikan Aman Bencana, SPAB). This community service program (PkM) aims to foster a culture of disaster preparedness in schools, enhance individual and institutional capacity to create safer learning environments, and spread disaster awareness through formal education. The PkM program began with coordination with the school principal to discuss technical implementation and evacuation route mapping. Training was conducted on Thursday, July 10, 2024, involving 30 teachers and staff. The training included disaster preparedness simulations, first aid (splinting), basic life support (BLS), and evacuation procedures. The outcomes included increased disaster awareness, the establishment of SPAB Standard Operating Procedures (SOPs), and forming a school command structure. Teachers were also trained to conduct school disaster risk assessments and develop SOPs for disaster mitigation and evacuation to enhance overall school safety.